2017
DOI: 10.1093/ptj/pzx010
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Different Activity Monitors to Count Steps in an Inpatient Rehabilitation Setting

Abstract: The StepWatch showed the highest accuracy and closest agreement with observed step count. This device can be confidently used by researchers for accurate measurement of step counts in inpatient rehabilitation in individuals who walk slowly. If immediate feedback is desired, the Fitbit One when worn on the ankle would be the best choice for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 25 publications
5
127
2
Order By: Relevance
“…A recent study comparing the accuracy of activity monitors worn on the wrist and the waist by people with PD performing short walks in a laboratory environment found that although the waist‐worn devices were more accurate, all devices underestimated step counts . Similarly, another study found that ActiGraphs worn on the waist were less than 80% accurate when participants walked at speeds between 0.8 and 1.2 m/s, with this accuracy decreasing further at slower walking speeds, possibly because of insufficient acceleration at the waist with slower swing‐through of the leg . Notably, in the present study, more time was recorded in slow walking (<1.04 m/s) by the waist monitor than the wrist monitor, suggesting that both monitors may be underestimating the amount of walking undertaken at slow speeds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study comparing the accuracy of activity monitors worn on the wrist and the waist by people with PD performing short walks in a laboratory environment found that although the waist‐worn devices were more accurate, all devices underestimated step counts . Similarly, another study found that ActiGraphs worn on the waist were less than 80% accurate when participants walked at speeds between 0.8 and 1.2 m/s, with this accuracy decreasing further at slower walking speeds, possibly because of insufficient acceleration at the waist with slower swing‐through of the leg . Notably, in the present study, more time was recorded in slow walking (<1.04 m/s) by the waist monitor than the wrist monitor, suggesting that both monitors may be underestimating the amount of walking undertaken at slow speeds.…”
Section: Discussionmentioning
confidence: 98%
“…To further analyze the effects of motor impairments, future studies could focus on attaining a larger sample, including participants with more severe impairments. This may also allow exploration to determine the contributions of PD impairments to the difference in step and activity counts in people with different clinical phenotypes of PD …”
Section: Discussionmentioning
confidence: 99%
“…Another issue is that most studies report having tested monitors accuracy over a short distance (15 m) with the monitor placed at the ankle while walking on level ground. Only one study investigated the validity of monitors in measuring step counts during the 6‐minute walk test (6MWT), among inpatients including some poststroke individuals . This may indeed represent the minimal distance required for outings in the community after discharge .…”
Section: Introductionmentioning
confidence: 99%
“…Activity monitors measure accelerations of the body segment to which the device is attached to, and the signal is filtered and pre‐processed by the monitor to obtain activity counts. Despite the advancements in technology, activity monitors can be inaccurate in capturing the activity of slow‐moving patients . A systematic review of 134 activity monitor‐based studies showed that accelerometers underestimate steps during slow walking by as much as 60% .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to validate these monitors in all study populations, i.e. people with visual impairment, not just older populations …”
Section: Introductionmentioning
confidence: 99%